Single-center experience and evaluation of rare ıntracranial abscesses in childhood - Nihal Yildiz; Zeynep Gökçe Gayretli Aydin (Italian Journal of Pediatrics)
Abstract Background Intracranial abscess (IA) is a rare disorder in childhood. Clinical manifestations of brain abscess include headache, fever, and focal neurological deficits. This study aimed to examine the demographic, clinical, laboratory, and imaging findings in children with IA. Methods Children admitted to the pediatric infection service with a diagnosis of IA between 2011 and 2022 were included in the study. Abscesses were divided into two groups: infratentorial and supratentorial. Demographic characteristics of the patients, complaints, MRI findings, and follow-up data were recorded and compared between the two groups. Results The study included a total of 23 patients, 9 (39.1%) of whom were male, with a mean age at diagnosis of 79.3 ± 65.4 months. The most common complaints were headache (39.1%), fever (91.3%), focal neurological deficits (60.9%), seizures, loss of consciousness (26.1%), and meningitis findings (60.9%). The most frequent etiology was post-operative procedures (30.4%), followed by a history of meningomyelocele (13%), and congenital heart disease (8.7%). On MRI, 68.7% of the supratentorial abscesses were multiple and commonly localized in the frontal and parietal regions. Treatment included ceftriaxone (82.6%), vancomycin (65.2%), meropenem (43.5%), metronidazole (34.8%), and linezolid (17.4%). The median hospitalization duration for patients was 32 days (range: 14–150). Of the patients, 34.8% were hospitalized and followed in the intensive care unit, and neurosurgery performed surgical interventions in 60.9% of cases, with evacuation in 21.7% of cases. In cultures, the causative agent was identified on average within 4 ± 1.3 days. Recurrence of abscess occurred in three (13%) cases, and 13% of cases had residual sequelae. Conclusions Intracranial abscess is a rare infectious disease that can result in long-term neurological deficits requiring extended follow-up and treatment. A correct and effective approach also positively impacts the prognosis of patients.